Fluorescence Spectroscopic Insight into the Supramolecular Interactions in DNA‐Based Enantioselective Sulfoxidation. (25th September 2018) - Cheng, Yu; Cheng, Mingpan; Hao, Jingya; Jia, Guoqing; Li, Can
Abstract: Interactions of copper(II)–bipyridine cofactors and thioanisole substrate with human telomeric G‐quadruplex DNA were studied by UV/Vis absorption, circular dichroism, and fluorescence quenching titration. Three copper(II)–bipyridine complexes are equivalently anchored to the G‐quadruplex scaffold at all five fluorescently labeled sites. Thioanisole interacts with the DNA architecture at both the second loop and 3′ terminus in the absence or presence of copper(II)–bipyridine complexes. These nonspecificities in the weak interactions of Cu II complexes and thioanisole with G‐quadruplex might explain why DNA only affords a modest enantioselectivity in the oxidation of thioanisole. These findings provide insights toward the construction of highly enantioselective DNA‐based catalysts. Abstract : Evenly spread : Fluorescence quenching titration was used to measure the supramolecular interactions of cofactor and substrate with a G‐quadruplex‐based DNAzyme. Copper(II)–bipyridine complexes are equivalently anchored to the G‐quadruplex scaffold at all five fluorescently labeled sites. Thioanisole substrate interacts with DNA at both the second loop and 3′ terminus in the absence or presence of the Cu II –bipyridine complexes.